2015
DOI: 10.1074/jbc.m115.638510
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic Acid Modulates the Plasticity and Inhibits the Motility of Breast Cancer Cells

Abstract: Background: All-trans-retinoic acid is a promising therapeutic agent in breast cancer. Results: All-trans-retinoic acid modulates mammary tumor cell epithelial-to-mesenchymal-transition via the TGF␤ and NOTCH pathways. Conclusion:The present study unveils a new aspect of all-trans-retinoic acid activity (i.e. regulation of phenotypic cell plasticity). Significance: Our results indicate that all-trans-retinoic acid is endowed with anti-metastatic properties that could be exploited at the therapeutic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 59 publications
(37 reference statements)
5
34
0
Order By: Relevance
“…In contrast to EMT inducers, atRA, known to also impair expression of drug transporters in hepatocytes in a major way [46], failed to reduce E-cadherin expression and to induce that of vimentin in HepaRG cells (Fig. 8A), which fully supports the fact that atRA does not favor EMT [47]. In addition, changes in profile of transporter mRNA expression induced by exposure to 5 µM atRA for 24 h, including down-regulation of OATP1B1 and OATP2B1 and up-regulation of NTCP and BCRP (Fig.…”
Section: Association Of Pma-induced Transporter Expression Changes Wisupporting
confidence: 69%
“…In contrast to EMT inducers, atRA, known to also impair expression of drug transporters in hepatocytes in a major way [46], failed to reduce E-cadherin expression and to induce that of vimentin in HepaRG cells (Fig. 8A), which fully supports the fact that atRA does not favor EMT [47]. In addition, changes in profile of transporter mRNA expression induced by exposure to 5 µM atRA for 24 h, including down-regulation of OATP1B1 and OATP2B1 and up-regulation of NTCP and BCRP (Fig.…”
Section: Association Of Pma-induced Transporter Expression Changes Wisupporting
confidence: 69%
“…ATRA is the first example of a clinically useful cyto-differentiating agent to be used in the treatment of acute promyelocytic leukemia (23). Now it is proposed as an antitumor agent not only in the context of hematological malignancies but also the chemo-prevention and treatment of many cancers including HCC (8)(9)(10)(11). In addition, it has been reported that ATRA could be used as a chemopreventive agent to inhibit the progression of premalignant lesions of the breast (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying the effect of ATRA on HCC are largely unknown. It has been revealed that ATRA can induce mesenchymal to epithelial transition of HCT116 cells (10), while ATRA modulates epithelial-to-mesenchymal-transition of mammary tumor cells via the TGFβ and NOTCH pathways (11). Thus, we raised a hypothesis that the anti-HCC effect of ATRA might be closely related to the reverse process of EMT.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has shown that in HER2-positive SKBR3 and UACC812 cells, there is an amplification of the ERBB2 and RARA genes and ATRA activated a RARα-dependent epithelial differentiation program. Moreover, ATRA blocked Notch-1 up-regulation by EGF and/or heregulin-β1 and switches TGFβ from an EMT-inducing and pro-migratory determinant to an antimigratory mediator [67] . ATRA can reduce the MS-forming ability of a subset of breast cancer cells, which correlates with induction of apoptosis, reducing SOX2 expression and inducing of its antagonist CDX2.…”
Section: Retinoids and Breast Cancermentioning
confidence: 99%